Analisis Rencana Strategi Pemasaran Layanan Unggulan Poli Mata Semarang Eye Center Di RSI Sultan Agung Semarang Tahun 2013 - Dian Saputro, Dicky; Suryawati, Chriswardani; Kartika Wulan, Lucia Ratna (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2014)
The number of visists the patient and increasing the SEC the last 5 years (2008-2012) and did not have plans on rencana stategik specific marketing strategies that needed to develop a marketing plan straegi SEC unit. The purpose of this study is to analyze the internal and external environment RSISA SEC unit based marketing mix is used as the basis for the preparation of marketing plans startegik SEC RSISA Unit.This research uses descriptive qualitative research approach. Subjects of the study were taken by purposive sampling techniques include nursing services and medical director, head of the division units SEC, marketing head of the division, in charge of field units SEC, two eye specialist doctors, nurses, medical and non-medical support personnel as the main respondents while two SEC service users as respondents triangulation. Analysis of the data using content analysis. The results showed the power that is the latest medical technology supporting facilities, strategic location, affordable rates and nonmedical medics good.Weaknesses are inadequate waiting area, promotion is not maximized, nurse jobs overlap. Opportunity that is a one-stop service, has partnerships with government and private institutions, and the provision of social activities. Threats owned unit layout SEC is located alongside the town, numbering queue is still manual. Strategic advice includes working with fendor-fendor medical devices, a partnership with both the private and government institutions, a larger installation of billboards, to enforce the one-stop service. From this study it can be suggested that the unit SEC to conduct an aggressive strategy for the advancement and development of the service